1961
DOI: 10.1063/1.1731693
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Resonance Absorption in Naphthalene in Its Phosphorescent State

Abstract: Paramagnetic resonance absorption has been observed in naphthalene in solid solution in a single crystal of durene when irradiated with light from an A-H6 mercury lamp. The fine structure of the spectrum at a frequency of ∼22.7×109 cps may be described by the spin-Hamiltonian H=|β|H·g·S+DSz2+E(Sx2−Sy2),,with S=1,g=2.0030±0.0004 (isotropic),D/hc=±0.1003±0.0006 cm−1,E/hc=∓0.0137±0.0002 cm−1.Observations at a different frequency, ∼9.7×109 cps, and also measurements on perdeuteronaphthalene are described by essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…Apart from spin correlation factors for the triplet state, this statement holds for most alternant molecules due to the pairing of bonding and antibonding molecular orbitals. The normalized spindensities in the lowest triplet state of naphthaleneare practically the same as those observed in the negative ion (Hutchison and Mangum, 1961 ;Carrington et af., 1959). The epr measurements of Vincent and Maki showed that the fine structure of the triplet state of quinoxaline is practically identical with that of the naphthalene triplet state (Vincent and Maki, 1963).…”
Section: E L E C T R O N P a R A M A G N E T I C R E S O N A N C E S supporting
confidence: 67%
“…Apart from spin correlation factors for the triplet state, this statement holds for most alternant molecules due to the pairing of bonding and antibonding molecular orbitals. The normalized spindensities in the lowest triplet state of naphthaleneare practically the same as those observed in the negative ion (Hutchison and Mangum, 1961 ;Carrington et af., 1959). The epr measurements of Vincent and Maki showed that the fine structure of the triplet state of quinoxaline is practically identical with that of the naphthalene triplet state (Vincent and Maki, 1963).…”
Section: E L E C T R O N P a R A M A G N E T I C R E S O N A N C E S supporting
confidence: 67%
“…1 and 2 are the atomic spin-orbit parameters of Cu 2+ and Cu 3+ , respectively. 3 to the wave function has such a small weight that the importance of this mechanism is negligible. At ϑ 1 ) 90°, only the 3d xy and 3d z 2 orbitals have nonzero copper contributions to the magnetic orbitals.…”
Section: Description Of the Dominant Mechanismsmentioning
confidence: 99%
“…I n the case of the 2-phenyl naphthalene, the results of the calculations were not unequivocal inasmuch as the calculated D* value was rather insensitive to the choice of @; in fact, all three sets of values for ,!I yielded results in good agreement with experiment for this molecule. This insensitivity in the calculation of D* for 2-phenyl naphthalene is probably due to the near-zero spin density at the 2 position of naphthalene in the triplet state [12]. AET is simply the difference between the observed and calculated values.…”
Section: Resultsmentioning
confidence: 99%